Rising star China's new security diplomacy - Gill, Bates; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2007)
"Analyzes the transformation in China's security diplomacy and makes the case for a more nuanced and focused policy toward Beijing. Focuses on Chinese policy in three areas--regional security mechanisms, nonproliferation and arms control, and questions of sovereignty and intervention. Concludes with recommendations for future U.S.-China relations"--Provided by publisher.
Includes bibliographical references (p. 217-250) and index.
Electronic reproduction.
Keywords: National security -- China; Nuclear nonproliferation -- China; China -- Foreign relations -- 1976-; China -- Foreign relations -- United States; United States -- Foreign relations -- China; Electronic books